Pengaruh Kepemimpinan dan Komunikasi terhadap Kinerja Karyawan pada PT. Duta Indah Global Kencana - Dewi Fitriyanti; Hendra Kurniawan; Syabrinildi Syabrinildi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine and analyze the influence of leadership and communication on employee performance at PT.Duta Indah Global Kencana. The population in this study were all employees of PT. Duta Indah Global Kencana totaling 56 people. The sampling technique used is using saturated samples. The data collection technique in this study uses a questionnaire distributed to employees of PT. Duta Indah Global Kencana. This study uses a quantitative method and the collected data is processed with SPSS 25. Data analysis techniques in this research use classical assumption tests, multiple regression, hypothesis testing and coefficient of determination. Based on the research results, it can be concluded that leadership and communication have a significant effect on employee performance.